Analisis Peningkatan Profitabilitas Petani Jamur Tiram Melalui Pengembangan Usaha Abon JamurTiram - Yuliana Mariya Ulva; Titi Rapini; Adi Santoso (ASSET: Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study was to determine the feasibility of developing the Oyster Mushroom business to be Oyster Mushroom Shredded to increase the profitability of the Oyster Mushroom Farmers and how much is the profitability of Oyster Mushroom farmers before and as young as the development of Shredded Oyster Mushrooms. The location of this study was the "CV. Maju Jaya" Oyster Mushroom Farmer in Jenangan sub-district, Ponorogo Regency.  The type of data used is secondary and primary data.  The analysis uses quantitative analysis for market and marketing aspects, Financial aspects and for qualitative analysis for Technical and Technology aspects, HR aspects, legal aspects. The results of this analysis of the market aspect have a great opportunity because only a few competitors are estimated to increase market share by 17% annually. On the technical aspect, the availability of raw materials is easily obtained because the location of production is one place with raw materials, equipment and machinery used that are already modern so as to speed up the production process. In the aspects of HRM, it has been planned that the workforce needs, organizational structure, salaries and employee skills improvement. In the legal aspect, analyzing the business in terms of business legality and explaining the home industry food acquisition procedure. Based on the analysis of the Fianasial aspect, it is feasible to do business development because it meets the investment criteria that are Net Present Value (NPV) of Rp. 156,603,848, Discounted Payback Period (  DPP), which is 3 years 3 months, and PI is 2.30, Internal Rate of Return (IRR) is 50.9%. Profitability prior to business development of Rp. 118,450,000 with ROI of 15% after developing a profitability business of Rp.  238,750,000 24%, then up by 9%. So that it can be concluded that the development of shredded Oyster Mushroom business to increase the profitability of Oyster Mushroom farmers is feasible to run.